Role of dopant ions in electrocatalytic oxidation of methanol using conducting polypyrrole electrodes - Radhakrishnan, S.; Adhikari, Arindam (Journal of Power Sources, 2006)
Conducting polypyrrole electrodes obtained by electro-polymerization of pyrrole on vacuum metallized glass substrates are modified by doping with a range of metal halides as dopant ions having different electronegativity. Electro-oxidation of methanol using these electrodes is studied by means of cyclic voltammetry in 0.1 M HCiO(4) as supporting electrolyte. It is found that the electronegativity of the dopant ion plays a very important role in the electrocatalytic activity. Polypyrrole doped with zirconium chloride gives the highest anodic current of 10 mA cm(-2) at the oxidation potential of methanol. The results are explained on the basis of the charge-transfer efficiency at the electrode I electrolyte interface, which is associated with the acceptor state created by the dopant in the semi-conducting polymer. (c) 2005 Published by Elsevier B.V.
Keywords: conducting polymers; electrocatalysis; fuel cells; Methanol oxidation; polypyrrole

Dopant induced effect on electrocatalytic reduction of nitrobenzene using conducting polypyrrole thin film electrodes - Adhikari, Arindam; Radhakrishnan, S. (Journal of Applied Polymer Science, 2011)
Conducting polypyrrole electrodes were prepared by electrochemical polymerization of pyrrole on vacuum-metallized glass substrates. These electrodes were modified by doping with a range of metal halides as dopant ions having different electronegativity. Electrochemical reduction of nitrobenzene using these electrodes was studied by means of cyclic voltammetry technique in acetonitrile medium containing aqueous HClO(4) (0.1M) as supporting electrolyte. It was found that the electronegativity of the dopant ion played a very important role in the electrocatalytic activity. Polypyrrole doped with nickel chloride gave the highest anodic current at the reduction potential of nitrobenzene. The results were explained on the basis of charge transfer efficiency at the electrode-electrolyte interface, which was associated with the acceptor state created by the dopant in the semi-conducting polymer. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 120: 719-724, 2011
Keywords: charge transfer; conducting polymer; Doping; electrocatalysis; nitrobenzene; polypyrrole; reduction

Significant enhancement of formic acid oxidation using rhodium nanostructures - Balan, Beena K.; Sathe, Bhaskar R. (Journal of Nanoscience and Nanotechnology, 2012)
The electrocatalytic activity of as-synthesized shape selective Rh nanostructures has been demonstrated using cyclic voltammetry, revealing unique shape-dependant performance towards HCOOH oxidation. interestingly, the enhancement factor (R) for different shapes of Rh with respect to that of commercial Rh towards formic acid oxidation ranges up to 20,000% for cubes as compared to 17,500% for pyramids and 11,000% for hexagons respectively. Mechanistic pathway for comparatively better sensitivity of cubes as compared to other shapes has been correlated with the results of X-ray diffraction.
Keywords: electrocatalysis; Formic Acid Oxidation; Preferential Growth; Rhodium Nanostructures

Facile single-step synthesis of nitrogen-doped reduced graphene oxide-Mn3O4 hybrid functional material for the electrocatalytic reduction of oxygen - Bag, Sourav; Roy, Kanak; Gopinath, Chinnakonda S.; Raj, C. Retna (ACS Applied Materials & Interfaces, 2014)
Development of efficient electrocatalyst based on non-precious metal that favors the four-electron pathway for the reduction of oxygen in alkaline fuel cell is a challenging task. Herein, we demonstrate a new facile route for the synthesis of hybrid functional electrocatalyst based on nitrogen-doped reduced graphene oxide (N-rGO) and Mn3O4 with pronounced electrocatalytic activity towards oxygen reduction reaction (ORR) in alkaline solution. The synthesis involves one-step in situ reduction of both graphene oxide (GO) and Mn(VII), growth of Mn3O4 nanocrystals and nitrogen doping onto the carbon framework using a single reducing agent, hydrazine. The X-ray photoelectron (XPS), Raman and FTIR spectral, and X-ray diffraction measurements confirm the reduction of GO and growth of nanosized Mn3O4. The XPS profile reveals that N-rGO has pyridinic (40%), pyrrolic (53%), and pyridine N oxide (7%) types of nitrogen. The Mn3O4 nanoparticles are single crystalline and randomly distributed over the wrinkled N-rGO sheets. The hybrid material has excellent ORR activity and it favors the 4-electron pathway for the reduction of oxygen. The electrocatalytic performance of the hybrid catalyst is superior to the N-rGO, free Mn3O4 and their physical mixture. The hybrid material shows an onset potential of -0.075 V, which is 60-225 mV less negative than that of the other catalyst tested. It has excellent methanol tolerance and high durability. The catalytic current density achieved with the hybrid material at 0.1 mg cm(-2) is almost equivalent to that of the commercial Pt/C (10%). The synergistic effect of N-rGO and Mn3O4 enhances the overall performance of the hybrid catalyst. The nitrogen in N-rGO is considered to be at the interface to bridge the rGO framework and Mn3O4 nanoparticles and facilitates the electron transfer.
Keywords: electrocatalysis; hybrid material; Mn3O4; nitrogen-doped graphene; oxygen reduction; synergistic effect

Cubic palladium nanorattles with solid octahedron gold core for catalysis and alkaline membrane fuel cell applications - Singh, Prem; Sonika; Gangadharan, Pranav K.; Khan, Ziyauddin; Kurungot, Sreekumar; Jaiswal, Amit (ChemCatChem, 2019)
Herein, we report the synthesis of palladium nanorattles (Au-Pd NRTs) comprising of a gold octahedral core caged within a thin porous cubic palladium shell. The introduction of core-shell and porous architecture was realized by combining seed mediated and galvanic replacement reaction techniques. Next, we examined the catalytic efficiency of the nanocatalyst in comparison with solid palladium nanocube (Pd-NC) of similar size for the degradation of p-nitrophenol and organic dyes. The rate constant of Au-Pd NRTs was found nearly 12 times higher than the Pd-NCs. Further, we exploited our catalyst for electrochemical oxygen reduction reaction (ORR) and observed its high intrinsic ORR activity. Compared with commercialized Pt/C, the Au-Pd NRT displayed nearly comparable onset and half-wave potential values and excellent durability upon potential cycling. The system level validation in a single-cell mode of alkaline exchange membrane fuel cell also confirms the efficiency of the present catalyst to serve as a potential cathode catalyst for realistic device applications.
Keywords: alkaline exchange membrane fuel cell; electrocatalysis; nanorattles; ORR; Pd nanoparticle

Structure-tailored non-noble metal-based ternary chalcogenide nanocrystals for pt-like electrocatalytic hydrogen production - Sarkar, Shreya; Rawat, Abhishek; Das, Tisita; Gaboardi, Mattia; Chakraborty, Sudip; Vinod, C. P.; Peter, Sebastian C. (ChemSusChem, 2021)
A facile microwave-assisted strategy was employed to synthesize Ni3Bi2S2 nanocrystals. Variation in the synthesis conditions tuned the composition of monoclinic and orthorhombic phases of Ni3Bi2S2. The electrochemical hydrogen evolution activity of the catalyst with highest percentage of monoclinic phase demonstrated a negligible onset potential of only 24 mV close to that of state-of-the-art Pt/C with an overpotential as low as 88 mV. Density functional theory calculations predicted the monoclinic phase exhibit the lowest adsorption free energy corresponding to hydrogen adsorption (Delta GadsH*) and, therefore, the highest hydrogen evolution activity amongst the considered phases. The quasi-2D structure of monoclinic phase facilitated an increased charge-transfer between Ni and Bi, favoring the downward shift of the d-band center to enhance the catalytic activity.
Keywords: charge transfer; electrocatalysis; hydrogen evolution reaction; Nanomaterials; ternary chalcogenides

Unveiling the roles of lattice strain and descriptor species on pt-like oxygen reduction activity in Pd-Bi catalysts - Sarkar, Shreya; Ramarao, S. D.; Das, Tisita; Das, Risov; Vinod, C. P.; Chakraborty, Sudip; Peter, Sebastian C. (ACS Catalysis, 2021)
A facile non-template-assisted mechanical ball milling technique was employed to generate a PdBi alloy catalyst. The induced lattice strain upon the milling time caused a shift of the d-band center, thereby enhancing the oxygen reduction reaction (ORR) catalytic activity. Additionally, the Pd-O reduction potential and adsorbed OH coverage used as descriptors stipulated the cause of the enhanced ORR activity upon the increased milling interval. Redox properties of surface Pd are directly correlated with a positive shift in the Pd-O reduction potential and OH surface coverage. Hence, by deconvoluting the lattice strain and the role of the descriptor species we achieved a catalyst system with a specific activity 5.4X higher than that of commercial Pt/C, as well as an improved durability. The experimental observation is well-corroborated by a theoretical simulation done by inducing strain to the system externally.
Keywords: charge-transfer; electrocatalysis; fuel cell; Lattice strain; oxygen reduction; Pt-like activity

Concurrent polyvalent interaction and electrocatalysis to improve lithium-sulfur battery performance - Kumar, Subramani; Krishnamoorthy, Kothandam (Batteries & Supercaps, 2022)
Batteries with improved efficiency are desired. Li-S batteries are attractive due to their high specific capacity and energy density. However, sluggish sulfur redox reaction and polysulfide dissolution are significant challenges in Li-S batteries. In this work, we report graphene with doped layer to electrocatalyze the sluggish sulfur redox reaction. The doped layer comprises heteroatoms such as either N or N and S. The doped layer also comprises cations of Ni. We have chosen a ``doped layer on graphene'' over ``doped graphene'' to avoid defects in the basal plane of graphene. We found the doped layer comprising graphene (DLC-G) to electrocatalyze the polysulfide redox reaction. However, the interaction between the doped layer and polysulfide is still weak, hence the dissolution is not suppressed. To circumvent the polysulfide dissolution, graphene with cationic layer was prepared. We found that cations in the layer electrostatically attract the polysulfides due to the polyvalent interaction. Thus, the dissolution is suppressed. While using this material in the Li-S batteries, the specific capacity, energy density and power density were found to be 1345 mAh g(-1), 782 Wh kg(-1) and 4437 W kg(-1), respectively.
Keywords: electrocatalysis; graphene; lithium-sulfur battery; mechanical exfoliation; polyvalent interaction

Alloying with Mn enhances the activity and durability of the CoPt catalyst toward the methanol oxidation reaction - Deshpande, Pooja; Prasad, Bhagavatula L. V. (ACS Applied Materials & Interfaces, 2023)
To improve the catalytic performance and durability ofPt catalystsused for the methanol oxidation reaction (MOR) in direct methanolfuel cells (DMFCs), alloying of Pt with other transition metals suchas Ru, Co, Ni, and Fe is considered an effective approach. Despitethe significant progress made in the preparation of bimetallic alloysand their utilization for MOR, improving the activity and durabilityof the catalysts to make them commercially viable remains a stiffchallenge. In this work, trimetallic Pt100-x (MnCo)( x ) (16 < x < 41) catalysts were successfully synthesized via borohydridereduction followed by hydrothermal treatment at 150 & DEG;C. The electrocatalyticperformance of the synthesized trimetallic Pt100-x (MnCo)( x ) (16 < x < 41) catalysts toward MOR was studied using cyclicvoltammetry and chronoamperometry. The results affirm that all Pt100-x (MnCo)( x ) (16 < x < 41) alloys have superior MOR activityand durability as compared to bimetallic PtCo alloys and commerciallyavailable Pt/C (comm. Pt/C) catalysts. Among all the compositionsstudied, the Pt60Mn1.7Co38.3/C catalystexhibited superior mass activity (1.3 and 1.9 times higher than thoseof Pt81Co19/C and comm. Pt/C, respectively)toward MOR. Furthermore, all the newly synthesized Pt100-x (MnCo)( x )/C (16 < x < 41) catalysts showed better CO tolerance when comparedwith comm. Pt/C. This improved performance of the Pt100-x (MnCo)( x )/C (16 < x < 41) catalyst can be attributed to the synergisticeffect of Co and Mn on the Pt lattice.
Keywords: CO tolerance; direct methanol fuel cells; electrocatalysis; methanol oxidation reaction(MOR); trimetallic alloy catalysts

Can metal cations electrocatalyze sulfur redox reaction and suppress polysulfide shuttle? - Kumar, Subramani; Swain, Gitanjali; Krishnamoorthy, Kothandam (Batteries & Supercaps, 2023)
In lithium-sulfur (Li-S) batteries, sulfur undergoes various changes. It switches between cyclic structure and linear structure. The charge on the sulfur varies between a neutral state and a negative charge-bearing state. Due to these changes, the sulfur/polysulfide dissolves in the battery electrolyte. Furthermore, the kinetics of the sulfur redox reaction is sluggish. Therefore, a material that can suppress sulfur/polysulfide dissolution and electrocatalyze sulfur redox reaction is needed. We hypothesize that the polysulfide dissolution can be suppressed if the host exhibits polyvalent electrostatic attraction. Polysulfide is a negative charge-bearing molecule; hence the host must comprise multiple positive charges. Nickel cations with other heteroatoms have been explored as a host in Li-S batteries. The heteroatoms impart additional interactions. The easier way to circumvent the effect of heteroatoms is the addition of metal salts. However, metal salts can either exhibit monovalent or divalent attraction with polysulfides. Those interactions are weak and we must have polyvalent interaction. Towards this objective, we have designed and synthesized a material that comprises multiple divalent cations that is also devoid of heteroatoms. The Li-S batteries fabricated using the metal cation immobilized graphene showed a maximum specific capacity of 1022 mAh/g at 0.1 C rate. Among the metal cations, nickel cations showed better performance than cobalt cations. Thus, we demonstrate that metal cations immobilized on Graphene can efficiently electrocatalyze the sluggish sulfur redox reaction and suppress the polysulfide dissolution.
Keywords: electrocatalysis; graphene; lithium-sulfur batteries; metal cations; polysulfides

Theory-directed designing of an intrinsic-activity-modulated metal-doped copper oxide electrode for nitrate to ammonia synthesis - Tyagi, Nitin Kumar; Mahapatra, Bikash K.; Ghimire, Suvash; Manna, Narugopal; Kumar, Deepak; Kumar, Vijay; Mukhopadhyay, Kausik; Singh, Santosh K. (ACS Applied Energy Materials, 2023)
Synthesis of ammonia via electrochemical reduction ofnitrate isone of the most sustainable routes both for environmental protectionas well as energy saving initiatives. However, this process is limitedto the development of high-performance free-standing catalytic electrodeswith improved selectivity and Faradaic efficiency. Herein, we reporttheory-guided designing and fabrication of free-standing non-noblemetal (Mn, Fe, and Co)-doped copper oxide (CuO) electrodes by usinga simple and scalable electrode preparation method. The density functionaltheory (DFT)-based calculations show that the doped-Co sites in theCu surface facilitate the generation and supply of H+ tothe adsorbed NO3 (-) during the reductionprocess; as a result, the Co-CuO catalyst displays higher selectivitytoward nitrate reduction. The Co-doped Cu electrode (Co-CuO)delivers a higher NH3 yield (5492 mu g cm(-2)) at a reduction potential of -0.91 V vs RHE while maintaininga Faradaic efficiency of >95%. The alloying of Co to the coppermetalnot only facilitates the proton donation to the adsorbed reactant(NO3 (-)) but also tunes the Cu d-center,resulting in the active site modulation responsible for the activationof catalysts.
Keywords: Active sites; ammonia synthesis; electrocatalysis; Faradaic efficiency; High selectivity; metal-doped electrode

Effect of transition metals (Mn, Co, Ni, and Zn) in size-controlled metal ferrite nanocrystals on the electrocatalytic oxygen evolution reaction - Jeyavani, Vijayakrishnan; Manoj, Shanmugasundaram; Mukherjee, Shatabdi Porel (ACS Applied Nano Materials, 2024)
Metal ferrite (MFO) M2+Fe2O4 (M2+ = Mn, Co, Ni, and Zn) nanocrystals (NCs) with a controlled size of similar to 4 nm were synthesized using stearic acid as the capping agent via a facile solvothermal method. The as-synthesized MnFe2O4 (MnFO), CoFe2O4 (CoFO), NiFe2O4 (NiFO), and ZnFe2O4 (ZnFO) NCs were characterized by XRD, FT-IR, Raman, XPS, TGA, TEM, and HRTEM analyses. The electrocatalytic oxygen evolution reaction (OER) is significant for future renewable energy to produce pure hydrogen (H-2) fuels through H2O splitting. However, because of the complex proton-coupled multielectron transfer process, it is kinetically quite challenging. Fe-containing transition metal-based electrocatalysts are well studied since it has been observed that Fe has a significant role in enhancing OER activity. It is well-known that the size and shape of the Fe/ferrite-based nanoelectrocatalyst play a vital role in electrocatalysis reactions. However, it is also critical to understand the effect of other earth-abundant and cost-effective transition metal ions (e.g., Mn, Co, Ni, and Zn) combined with Fe/ferrite NC-based OER electrocatalytic reactions while keeping the size of NCs constant and compare their electrocatalytic properties toward the development of advanced nanoelectrocatalysts, which is rarely studied to the best of the authors knowledge. Therefore, herein, the electrocatalytic properties for OER were examined by using the as-synthesized MnFO, CoFO, NiFO, and ZnFO NCs to understand the effect of metal ions (Mn, Co, Ni, and Zn) on the Fe-based nanoelectrocatalysts by keeping the size of the nanoelectrocatalysts constant at similar to 4 nm. Additionally, the influence of different substrates, e.g., carbon paper (CP) and nickel foam (NF), on the electrocatalytic activity of MFO (MnFO, CoFO, NiFO, and ZnFO) NCs was also compared. Interestingly, as an OER nanoelectrocatalyst, the CoFO NCs on the CP substrate show better electrochemical OER activity than other MFO NCs, with a Tafel slope value of 49.4 mV dec(-1), an ECSA of 112 cm(2), and a long-term stability of 24 h, which is comparatively higher than the other as-synthesized MFO NCs. On the other hand, MnFO NCs on the NF substrate show better electrochemical OER activity than the other as-synthesized MFO NCs. Therefore, this work highlights the effect of the substrate and the influence of transition metals, e.g., Mn, Co, Ni, and Zn, on size-controlled Fe-based nanoelectrocatalysts toward developing advanced OER electrocatalysts.
Keywords: Carbonpaper; electrocatalysis; Ferrites; Nickel foam; Oxygen Evolution Reaction; Size-controlled nanocrystals

Electrocatalytic glycerol conversion: a low-voltage pathway to efficient carbon-negative green hydrogen and value-added chemical production - Chauhan, Inderjeet; Bajpai, Himanshu; Ray, Bishakha; Kolekar, Sadhu K.; Datar, Suwarna; Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (ACS Applied Materials and Interfaces, 2024)
Electrochemical glycerol oxidation reaction (GLYOR) could be a promising way to use the abundantly available glycerol for production of value-added chemicals and fuels. Completely avoiding the oxygen evolution reaction (OER) with GLYOR is an evolving strategy to reduce the overall cell potential and generate value-added chemicals and fuels on both the anode and cathode. We demonstrate the morphology-controlled palladium nanocrystals, afforded by colloidal chemistry, and their established morphology-dependent GLYOR performance. Although it is known that controlling the morphology of an electrocatalyst can modulate the activity and selectivity of the products, still it is a relatively underexplored area for many reactions, including GLYOR. Among nanocube (Pd-NC), truncated octahedron (Pd-TO), spherical and polycrystalline (Pd-PC) morphologies, the Pd-NC electrocatalyst deposited on a Ni foam exhibits the highest glycerol conversion (85%) along with 42% glyceric acid selectivity at a low applied potential of 0.6 V (vs reversible hydrogen electrode (RHE)) in 0.1 M glycerol and 1 M KOH at ambient temperature. Owing to the much favorable thermodynamics of GLYOR on the Pd-NC surface, the assembled electrolyzer requires an electricity input of only similar to 3.7 kWh/m(3) of H-2 at a current density of 100 mA/cm(2), in contrast to the requirement of >= 5 kWh/m(3) of H-2 with an alkaline/PEM electrolyzer. Sustainability has been successfully demonstrated at 10 and 50 mA/cm(2) and up to 120 h with GLYOR in water and simulated seawater.
Keywords: electrocatalysis; Glycerol; green hydrogen; nanocube; Palladium; SDG

Electrodeposited Co-Mn-Sn multicomponent alloy as an efficient electrocatalyst for hydrogen evolution reaction - Chandran, M. Athira; Karumuthil, Subash Cherumannil; Singh, Ashutosh K.; Prasad, Bhagavatula L. V. (International Journal of Hydrogen Energy, 2024)
Despite having exciting material characteristics, the potential of multi-component alloys (MCAs) as electrocatalysts has not been fully realized. In this work, efficient binary and ternary MCA electrocatalysts containing inexpensive metals like Co, Mn and Sn have been prepared via the electrodeposition process. When tested for hydrogen evolution reaction (HER) in an alkaline medium, ternary Co-Mn-Sn alloy displayed enhanced activity with the lowest overpotential of 136 mV, a Tafel slope of 111 mV dec 1 and a very low charge transfer resistance, making it superior to the binary alloys (Co-Mn and Co-Sn), or the single metal catalysts (Co, Mn and Sn). The ternary alloy also displayed high electro-chemical and structural stability, making it a viable electrocatalyst for the hydrogen economy.(c) 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Clean energy; electrocatalysis; Electrodeposition; hydrogen evolution reaction; Multi-component alloy; Non-platinum group metals

Establishing a new efficiency descriptor for methanol oxidation reaction and its validation with commercially available Pt-based catalysts - Deshpande, Pooja S.; Radhakrishnan, Thulasi; Prasad, Bhagavatula L. V. (Fuel Cells, 2024)
Direct methanol fuel cells (DMFCs) have received a lot of attention in recent years as promising technology for generating clean and efficient energy. In DMFC, the anode catalyst is a vital component because it is involved in the oxidation of methanol, which produces electrons that can be used as an energy source. Cyclic voltammetry (CV) is commonly used to test the characteristics of the electrode materials before they are employed in the actual fuel cell. Interestingly in the case of DMFCs CV also is a useful technique to obtain vital information about the performance and expected efficiency of the electrodes. In general, the CV of methanol electrooxidation for Pt-based catalysts has two peaks, If in the forward scan (anodic scan) and Ib in the backward scan (cathodic scan). The ratio of these two peaks (If/Ib) is the most commonly used criterion for investigating CO poisoning in catalysts. However, there is a great deal of ambiguity surrounding this criterion, owing to the genesis of Ib. Addressing this we present here a new criterion to evaluate the efficiency of the catalyst using the same CV technique. We validate this newly proposed criterion with commercial Pt/C (comm. Pt/C) and other commercially available alloy catalysts.
Keywords: catalyst poisoning; CO tolerance; direct methanol fuel cells; electrocatalysis; Methanol oxidation reaction

Europium oxide on carbon nitride for electrocatalytic glycerol oxidation coupled with hydrogen evolution reaction - Jana, Jayasmita; Sharma, Tata Sanjay Kanna; Ghanem, Mohamed A.; Choi, Won Mook; Gopinath, Chinnakonda S.; Hur, Seung Hyun (Separation and Purification Technology, 2025)
{The integration of the electrochemical glycerol oxidation reaction (GOR) with the hydrogen evolution reaction (HER) has emerged as a promising alternative to the sluggish oxygen evolution reaction (OER) in water splitting toward the development of renewable and clean energy sources. However, suitable electrodes that facilitate redox kinetics while increasing the selectivity of the desired product(s) are still required. Herein, a series of europium oxide (Eu2O3) anchored on graphitic carbon nitride (g-CN) nanoaggregates (g-CNEux
Keywords: carbon support; electrocatalysis; Glycerol; HER; Rare earth metal

Platinum-free electrocatalysts based on electrodeposited Co-Mn-Ni alloys for efficient electrocatalytic alkaline water splitting - Chandran, M. Athira; Dutta, Pritha; Singh, Ashutosh K.; Prasad, Bhagavatula L. V. (ACS Applied Energy Materials, 2025)
The development of a Pt-free electrocatalyst for efficient and stable water splitting is crucial for the commercialization of green hydrogen production. A low-cost electrocatalyst with good hydrogen and oxygen evolution activities (HER and OER, respectively) displaying long durability is the first step in this direction, and if the catalyst can be synthesized via an easy, convenient, and scalable procedure, that would be an added advantage. Multicomponent alloys, with their tunable compositions and abundant active sites, present a promising solution in this direction. Herein, a cost-effective CoMnNi (CMN) alloy is synthesized via electrodeposition and with optimized composition by tuning the electrolyte concentration and deposition potential to enhance electrocatalytic performance. The resulting single-phase alloy exhibits a high electrochemical surface area with an average particle size of similar to 4 nm, demonstrating excellent hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) activities in 1 M KOH, with overpotentials of 121 mV at -10 mA cm-2 and 285 mV at 20 mA cm-2, respectively. Moreover, the catalyst exhibits remarkable stability, sustaining 100 h of operation at 100 mA cm-2. The CMN alloy also performs efficiently under harsh conditions, including 6 M KOH and alkaline seawater, in both symmetric and asymmetric cell configurations. This work highlights the potential of multicomponent alloys as durable, high-performance electrocatalysts for scalable water splitting, paving the way for sustainable hydrogen production.
Keywords: alkaline seawater; electrocatalysis; Electrodeposition; hydrogen evolution reaction(HER); multicomponentalloy; oxygen evolution reaction (OER); stability; watersplitting

Synergistic MoS2@MWCNT nanocomposites for high-efficiency catalysis and energy applications - Auti, P. S.; Kanawade, R. V.; Alshehri, S. A.; Warule, S. S.; Shin, D. K.; Yewale, M. A. (Chemical Physics Letters, 2025)
The MoS2-MWCNT composite heterojunction for its potential as an electrocatalyst and energy storage material. The composite demonstrated remarkable electrochemical performance, achieving a specific capacitance of 263 F/g, an energy density of 16.89 Wh/kg, and a power density of 478 W/kg. Using CV profiles, we analyzed the charge storage mechanism and found that the anodic and cathodic processes had b values of 0.48 and 0.45, respectively, indicating diffusion-controlled behavior. Diffusion coefficients of 6.44 x 10(-7) cm(2)/s (anodic) and 11.32 x 10(-7) cm(2)/s (cathodic) confirmed this mechanism. In the constructed device using MoS2-MWCNT and activated carbon (AC), we observed a specific capacitance of 18.71 F/g, an energy density of 5.09 Wh/kg, and a power density of 833 W/kg. After stability, testing, electrochemical impedance spectroscopy (EIS) revealed a slight increase in series resistance, rising from 2.33 Omega to 2.49 Omega. The MoS2-MWCNT composite also exhibited excellent electro catalytic performance. For the hydrogen evolution reaction (HER), it achieved an over potential of 0.221 V and a Tafel slope of 0.321 V/dec. After stability testing, we measured Rs and Rct values of 4.86 Omega and 2.57 Omega, respectively. For the oxygen evolution reaction (OER), the composite showed an over potential of 597 mV and a Tafel slope of 0.285 V/dec, with post-stability Rs and Rct values of 5.63 Omega and 5.57 Omega, respectively. These findings highlight the versatility of the MoS2-MWCNT composite for applications in energy storage and water splitting.
Keywords: electrocatalysis; hydrothermal; MoS2-MWCNT; supercapacitor; TEM; XPS

Concurrent glycerol oxidation and hydrogen production on Ce-Co oxide/carbon for sustainable biomass valorization - Jana, Jayasmita; Chowdhury, Somnath; Saha, Avishek; Kang, Sung Gu; Hur, Seung Hyun; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2026)
Integrating glycerol oxidation with water electrolysis offers a sustainable route for hydrogen production while enabling concurrent generation of industrially relevant C1-C3 value-added materials. This system replaces kinetically sluggish oxygen evolution reaction (OER) simultaneously delivering H-2 at the cathode with high turnover frequency, thereby lowering the overall cell voltage and enabling the valorization of glycerol, a major by-product of the biodiesel industry. However, the development of an efficient bifunctional electrocatalysts capable of driving cathodic as well as anodic half-cell reactions remains a key challenge. Herein, we present a cerium-cobalt oxide composite modified with an amorphous carbon layer (Ce,Co-O/C) as an effective bifunctional catalyst for glycerol-assisted water electrolysis. The interfacial electron distribution across the Co-Ce oxide heterojunction generated abundant redox-active sites and accelerates reaction kinetics, while the conductive carbon layer facilitates rapid charge transfer and imparts improved stability. Consequently, the Ce, Co-O/C catalyst exhibited high formate selectivity at 1.4 V (vs RHE) at room temperature and delivers a low cell voltage of 1.90 V at 100 mA cm(-2) in a symmetric Ce,Co-O/C vertical bar vertical bar Ce,Co-O/C system, maintaining operational stability over 100 h. This work provides a promising interface-engineering for designing self-supported bifunctional electrocatalysts toward integrated biomass assisted co-electrolysis systems.
Keywords: Amorphous carbon; biomass valorization; electrocatalysis; energy conversion; green hydrogen

Potential tuneable glucose oxidation to selective C6 molecules and CC cleavage, and parallel green H2 production: sustainable high current density electrolysis - Chauhan, Inderjeet; Patra, Kshirodra Kumar; Vijay, Pothoppurathu M.; Nalajala, Naresh; Mehta, Shweta; Joshi, Kavita; Ravindranathan, Sapna; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2026)
Current study elucidates the electrocatalytic efficacy of palladium-nanocubes (Pd-NCs) for the selective oxidation of glucose to value-added chemicals with concomitant hydrogen evolution. The Pd-NC catalyst demonstrated exceptional activity and product selectivity, achieving nearly quantitative glucose conversion (>99 %) with high gluconic and glucaric acid yield at low anodic overpotential (0.6 V vs. RHE) in alkaline electrolyte. At not-so-high elevated potentials (1.2 V vs. RHE), oxidative CC scission prevails, yielding shorter-chain carboxylates along with C6-acids. Reaction products are thoroughly characterized and quantitatively estimated by NMR spectral methods; NMR methods also provide CC cleavage and mechanistic pathways of glucose to various products. Complementary DFT calculations delineate the thermodynamic favorability of glucose adsorption on Pd-NC surfaces (-1.83 eV) and the exergonic oxidation pathway under applied bias, corroborating experimental product distributions. In a two-electrode electrolyzer, Pd-NC anode paired with Pt/C and Ni2P cathode demonstrates 100 mA/cm(2) at 0.99 V and 1.37 V, respectively, with 48 % reduction in energy input (26.6 kWh/kg H-2) compared to conventional alkaline electrolysis; critically, H-2 production energy is lower than the usable energy (33.3 kWh/kg H-2). Sustainable chronopotentiometric assays confirm sustainability (similar to 140 h) in alkaline as well as saline electrolytes, underscoring the system's resilience against chloride-mediated corrosion. Present work establishes a proof of concept for integrated biomass-component valorization and carbon-negative green hydrogen production, merging atomic-level mechanistic insights with scalable reactor design. Optimization of reaction parameters, including potential tuning, reaction temperature and electrolyte engineering, offers a compelling strategy to further enhance C6 and fragmented product selectivity and overall system efficiency.
Keywords: biomass valorization; electrocatalysis; energy conversion; Sustainability

Silico imine-based ligand engineering of CALF-20 for electrocatalytic ammonia production - Samudre, Nikhil S.; Samal, Pragnya Paramita; Krishnamurty, Sailaja (ACS Sustainable Chemistry & Engineering, 2026)
Electrocatalytic ammonia synthesis is emerging as a globally compelling, sustainable alternative to the Haber-Bosch process under ambient conditions. As a result, active-site engineering has taken center stage in the development of stable and effective electrocatalysts. In this work, we report how the introduction of an imine group in the ligand backbone of CALF-20, a Zn-based, moisture-stable MOF with high surface area, results in the formation of an N-4 macrocycle for transition-metal anchoring. PBE + D3 calculations, supported by spectroscopic, ab initio molecular dynamics, and electronic analyses, identify Fe-bound modified CALF-20 as the most stable configuration among the Mn-, Fe-, Co-, Ni-, Cu-, Ru-, Rh-, Ag-, and Au-anchored within the modified CALF-20 framework. Upon modification, the d-band center shifts from -5.08 to -4.44 eV in M-Fe-CALF-20. Adsorption studies confirm activation of both N-2 and NO2, reflected by bond elongation and red-shifted IR peaks. Mechanistic studies show that M-Fe-CALF-20 selectively facilitates NH3 formation, exhibiting PDS values of 0.69 and 0.62 eV for the NRR and NO2RR, respectively, while a competitive adsorption shows a clear preference over HER. Our study illustrates how functionalization tunes CALF-20 for dual application as an adsorbent and as an electrocatalyst for NH3 synthesis and storage.
Keywords: Adsorption; CALF-20 MOF; electrocatalysis; hydrogen evolution reaction; nitrogen oxide reductionreaction (NO2RR); nitrogen reductionreaction